2022
DOI: 10.1108/ijchm-12-2021-1525
|View full text |Cite
|
Sign up to set email alerts
|

The perils of hospitality internship: a growth curve approach to job motivation change

Abstract: Purpose Why would a hospitality or tourism enterprise’s talent program backfire to demotivate interns from engaging in their jobs? This study aim to synthesize theoretical strands from the self-determination theory, person–environment fit theory and conservation of resources theory to investigate the predictors of perceived person–job fit and how such a fit causes changes in interns’ job motivation over time. Design/methodology/approach A four-wave longitudinal study was conducted. The four waves of data obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Thus, the existence of work motivation will make a person better prepare himself. VE must be able to motivate in order to prepare graduates who are ready to work because basically work motivation is one of the factors that make students able to make logical considerations (Xu et al, 2022). The lower the motivation to work will cause the work readiness of students to be low.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the existence of work motivation will make a person better prepare himself. VE must be able to motivate in order to prepare graduates who are ready to work because basically work motivation is one of the factors that make students able to make logical considerations (Xu et al, 2022). The lower the motivation to work will cause the work readiness of students to be low.…”
Section: Discussionmentioning
confidence: 99%
“…In hospitality organizations, where employees face high expectations for quality service and often work in high-pressure environments (Kalargyrou et al , 2023; Liu-Lastres et al , 2023; Mohsin et al , 2023; Wallace and Coughlan, 2023; Xu et al , 2023), perceptions of WF can play a crucial role in helping employees’ recovery and maintain their well-being, as well as in promoting favorable work attitudes and performance. For example, Tews et al ’s (2013) research on US employees revealed that fun activities and managerial support of fun enhanced employee performance and decreased their turnover intentions.…”
Section: Literature Review and Study Hypothesesmentioning
confidence: 99%
“…For instance, according to Wen et al (2019), the proportion of hospitality management students in China who ultimately pursue careers in hotels ranges from 10% to 20%. In addition to the fact that occupational stigma can detrimentally affect the retention intentions of hospitality management students (Wen et al , 2019), inadequately supervised internships can also result in the potential departure of highly skilled individuals from the hotel and tourism sectors (Xu et al , 2023).…”
Section: Introductionmentioning
confidence: 99%